Kognitiv lingvistika: asosiy tushunchalar va nazariyalar - Tashxujayeva Nigora Madaminjanovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
The article explores the evolving field of cognitive linguistics, highlighting its historical roots and contemporary relevance. It posits that language serves not only as a tool for communication but also as a fundamental component of human cognition and cultural identity. By examining key processes such as conceptualization and categorization, the article illustrates how language encodes human experiences and structures our understanding of the world. It emphasizes the interdisciplinary connections of cognitive linguistics with psychology, anthropology, and cultural studies, while acknowledging the limitations of qualitative analyses in the field. The article concludes by suggesting future research directions that could integrate empirical methodologies and cross-cultural studies, ultimately enriching our understanding of the dynamic interplay between language, thought, and culture.